1987
DOI: 10.1002/cbf.290050405
|View full text |Cite
|
Sign up to set email alerts
|

A critical evaluation of the use of filipin‐permeabilized rat hepatocytes to study functions of the endoplasmic reticulum in situ

Abstract: We have used transmission (TEM) and scanning electron microscopy (SEM) and leakage of lactate dehydrogenase (LDH; EC 1.1.1.27) to evaluate two published procedures which use filipin to render isolated rat hepatocytes permeable to ionic substrates. Cells treated by the procedure of Jorgenson and Nordlie retained less than 10 per cent of their LDH. TEM revealed severe damage to the internal structure of these cells, which included swelling, disintegration and extensive vesicularization of the endoplasmic reticul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…4 demonstrate that the observed reduction in diabetic porous-cell G6P metabolism in the optimal range (40-70% porous) did not result from a subtle impairment in substrate ingress relative to control cells, because the differences also persisted in the highest range (70-95% porous). That optimal metabolic activity and cellular LDH retention occurred when <100% of the adipocytes were visually fluorescent is similar to the finding of McEwen et al (51) with trypan blue staining of permeabilized hepatocytes. As McEwen et al suggested, porous-cell G6P entry may be unrestricted despite insufficient dye accumulation for visual detection.…”
Section: Discussionsupporting
confidence: 83%
“…4 demonstrate that the observed reduction in diabetic porous-cell G6P metabolism in the optimal range (40-70% porous) did not result from a subtle impairment in substrate ingress relative to control cells, because the differences also persisted in the highest range (70-95% porous). That optimal metabolic activity and cellular LDH retention occurred when <100% of the adipocytes were visually fluorescent is similar to the finding of McEwen et al (51) with trypan blue staining of permeabilized hepatocytes. As McEwen et al suggested, porous-cell G6P entry may be unrestricted despite insufficient dye accumulation for visual detection.…”
Section: Discussionsupporting
confidence: 83%
“…To further examine how ER morphology affects the ERES patterns, we sought for possibilities to convert the ER into a set of disjoint fragments. As a first means, we applied filipin to otherwise untreated cells (see Materials and methods), which led to a disintegration of the ER as previously described (38,50). As a result of the treatment, each cell displayed, on average, $700 ER fragments with a typical apparent area in the range of 0.6 mm 2 , i.e., they were on average markedly larger than ERESs in untreated cells (Fig.…”
Section: Altered Er Morphologies Impact On Eres Patternsmentioning
confidence: 99%
“…Filipin has often been used as a permeabilizing agent (16) and has an ionophorous action on lipid bilayers (15,37). Thus in intact lung preparations, increased membrane permeability of any contaminant 125 I that is not associated with albumin could conceivably reduce or mask an inhibitory effect of filipin on 125 I-albumin uptake.…”
Section: Studies In the Intact Lung Preparation In Support Of The Tramentioning
confidence: 99%